The application of atomic force microscopy in the surface analysis of polymeric biomaterials - Shakesheff, Kevin (1995)
When a polymeric biomaterial is employed within a living system an interface is created between the solid surface of the polymer and an aqueous environment. The processes that occur at this interface will determine if the biomaterial is accepted by the patient and often will determine if the specific function of the biomaterial can be achieved. Increasingly, novel biomaterials are expected to perform more sophisticated functions and, therefore, their surfaces must be designed to realize precise interfacial events, such as specific interactions with proteins and cells or controlled biodegradation.